2018
DOI: 10.2147/jmdh.s150623
|View full text |Cite
|
Sign up to set email alerts
|

Ruralization of students’ horizons: insights into Australian health professional students’ rural and remote placements

Abstract: IntroductionHealth workforce shortages have driven the Australian and other Western governments to invest in engaging more health professional students in rural and remote placements. The aim of this qualitative study was to provide an understanding of the lived experiences of students undertaking placements in various nonmetropolitan locations across Australia. In addition to providing their suggestions to improve rural placements, the study provides insight into factors contributing to positive and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 32 publications
0
78
0
Order By: Relevance
“…They concluded that the 'ruralisation of students' horizons' was the core construct that represented the importance of preparing health professional students for practice in non-metropolitan locations. 4 This preparation or 'ruralisation of horizons' was reflected by new-graduates in this study, who felt that prior exposure to the setting would enhance awareness of the adaptations required for effective practice. This is despite over half of the cohort having previously lived in a rural or remote setting, suggesting that specific health care relevant exposure might be beneficial.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…They concluded that the 'ruralisation of students' horizons' was the core construct that represented the importance of preparing health professional students for practice in non-metropolitan locations. 4 This preparation or 'ruralisation of horizons' was reflected by new-graduates in this study, who felt that prior exposure to the setting would enhance awareness of the adaptations required for effective practice. This is despite over half of the cohort having previously lived in a rural or remote setting, suggesting that specific health care relevant exposure might be beneficial.…”
Section: Discussionmentioning
confidence: 84%
“…Smith et al 4 provided an understanding of the lived experience of students across a range of disciplines undertaking placements in various non-metropolitan locations across Australia. They concluded that the 'ruralisation of students' horizons' was the core construct that represented the importance of preparing health professional students for practice in non-metropolitan locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown the shortage of health care professionals working in Australia, predominantly in rural Australia, though the main focus of these studies has been on shortages and the maldistribution of doctors (2)(3)(4)(9)(10)(11)(12)(13)(14). Some of these studies have also included allied health professionals (12,13), but dental professionals appear underrepresented in the literature (3,15,16).…”
Section: Introductionmentioning
confidence: 99%